The Effectiveness of Role-Playing Techniques in Group Guidance Services to Improve Academic Hardiness - Nadya Ayu Sukmawati; Aprilia Setyowati; Amien Wahyudi; Rohmatus Naini (Journal of Education and Counseling (JECO), 2026)
The low level of academic hardiness among junior high school students in coping with academic pressure indicates the need for interventions that can strengthen students’ resilience in academic settings. This study aimed to examine the effectiveness of group guidance services using role-playing techniques in improving students’ academic hardiness. A quantitative approach with a pre-experimental one-group pretest–posttest design was employed. The participants consisted of 8 students selected based on their academic hardiness levels. Data were collected using an Academic Hardiness Scale developed based on Kobasa’s theory, encompassing the dimensions of commitment, control, and challenge. The instrument was tested using the Rasch model and demonstrated good measurement quality, with person reliability of .90, item reliability of .99, and Cronbach’s Alpha of .92. Group guidance services using role-playing techniques were conducted in four sessions to strengthen students’ commitment, control, and challenge in dealing with academic demands. Data were analyzed using the Shapiro–Wilk normality test and a paired sample t-test. The findings indicated that group guidance services using role-playing techniques were effective in improving students’ academic hardiness. These findings suggest that role-playing can be implemented as a practical strategy in group guidance services to help students strengthen resilience, maintain learning commitment, and cope more effectively with academic pressure.